2002
DOI: 10.1002/dvdy.10157
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of Wnts, Frizzleds, sFRPs, and misexpression in transgenic mice suggesting a role for Wnts in pancreas and foregut pattern formation

Abstract: It is well established that gut and pancreas development depend on epithelialmesenchymal interactions. We show here that several Wnt, Frizzled, and secreted frizzled-related protein (sFRP) encoding mRNAs are present during mouse pancreatic morphogenesis. Wnt5a and 7b mRNA is broadly expressed in foregut mesenchyme starting around embryonic day 10 in mice. Other members expressed are Wnt2b, Wnt5b, and Wnt11. In addition, genes for the Wnt receptors, Frizzled2, 3, 4, 5, 6, 7, 8, and 9 are expressed. To understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
141
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(152 citation statements)
references
References 55 publications
7
141
1
2
Order By: Relevance
“…To test whether Wnt signaling controls islet ␤ cell growth, we exposed isolated pancreatic islets to purified Wnt3a, a Wnt family member that is expressed in the developing pancreas and in adult human islets (15). In prior studies we showed that purified Wnt3a led to ␤-catenin stabilization and induction of established Wnt target genes (16).…”
Section: Resultsmentioning
confidence: 99%
“…To test whether Wnt signaling controls islet ␤ cell growth, we exposed isolated pancreatic islets to purified Wnt3a, a Wnt family member that is expressed in the developing pancreas and in adult human islets (15). In prior studies we showed that purified Wnt3a led to ␤-catenin stabilization and induction of established Wnt target genes (16).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Wnt signalling molecules and Frizzled receptors are expressed in the endocrine pancreas of both mice and humans [12,16,33] and regulate insulin secretion [17] and beta cell proliferation [19]. In contrast, the canonical Wnt signalling pathway cannot be activated in glucagon-producing alpha cells [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…At this early stage, FGF10 treatment of dorsal pancreatic endoderm explants was sufficient to increase the expression of Ptf1a, a transcription factor needed to complete pancreatic specification (36,37). Thus, one possibility is that early FGF10 misexpression in the pancreas modifies the pancreatic cell-differentiation program, a mechanism recently suggested to explain the pancreatic phenotype of mice that overexpress Wnt1 under the control of the Pdx1 promoter (38). These mice have pancreatic agenesis.…”
Section: Discussionmentioning
confidence: 97%